Evaluation of Leishmanization Using Iranian Lizard Leishmania Mixed With CpG-ODN as a Candidate Vaccine Against Experimental Murine Leishmaniasis - Keshavarzian, Nafiseh; Noroozbeygi, Mina; Haji Molla Hoseini, Mostafa; Yeganeh, Farshid (Frontiers in Immunology, 2020)
Background and objectives: Development of a vaccine against leishmaniasis, which is able to induce protective immune responses, is an important objective. The live non-pathogenic lizard parasites have recently provided a promising new approach to develop a vaccine against leishmaniasis.Methods: Four groups of female BALB/c mice were examined in the study: group 1 received PBS, group 2 received CpG, group 3 received 2×10 5 Iranian Lizard Leishmania (ILL) promastigotes and group 4 received ILL mixed with CpG (ILL+CpG). All injections were carried out subcutaneously in the right footpad. Three weeks later, all mice were challenged in the left footpad with 2×10Leishmania major EGFP metacyclic promastigotes. Footpad swelling and in vivo fluorescent imaging was used to evaluate infection progress and relative parasite burden during infection course. Eight weeks after challenge, all mice were sacrificed and the cytokines levels (IFN-γ, IL-4 and IL-10) and antibodies concentrations (IgG2a and IgG1) using ELISA assay, nitric oxide production using Griess assay and arginase activity in splenocytes culture, were measured. In addition, qPCR assay was performed to quantify the splenic parasite burden.The results showed that mice immunized with ILL+CpG were protected against the development of dermal lesion and showed a reduction in the spleen parasite load in comparison with control groups. This protection was associated with higher production of IFN-γ, as well as reduction of IL-4. Additionally, the results demonstrated that arginase activity was decreased in ILL+CpG group compared to other groups.ILL with an appropriate adjuvant would be a suitable choice for vaccination against leishmaniasis.